2020
DOI: 10.1002/npr2.12155
|View full text |Cite
|
Sign up to set email alerts
|

Psycho‐educational interventions focused on maternal or infant sleep for pregnant women to prevent the onset of antenatal and postnatal depression: A systematic review

Abstract: Aims This systematic review aimed to evaluate randomized controlled trials (RCTs) to examine the effect of maternal and infant sleep intervention during women's pregnancy for the purpose of preventing perinatal depression. Method A systematic search (from inception to January 28, 2019) for RCTs using five electronic databases—the Cochrane Controlled Register of Trials (CENTRAL), Embase, PubMed, PsycINFO, and Ichushi Web (Japan Medical Abstracts Society)—was conducted. Twelve investigators independently conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Our results are in line with this latter body of studies that corroborate the socio-emotional selective theory [132,133] stating that getting older can lead workers to focus on positive emotions and memories rather than on negative information, which, in turn, can contribute to maintaining their well-being. Additionally, women reported higher levels of depressive mood and anxiety symptoms, which is in line with previous research on this topic showing women's greater susceptibility to stress and psychological health symptoms [134][135][136].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in line with this latter body of studies that corroborate the socio-emotional selective theory [132,133] stating that getting older can lead workers to focus on positive emotions and memories rather than on negative information, which, in turn, can contribute to maintaining their well-being. Additionally, women reported higher levels of depressive mood and anxiety symptoms, which is in line with previous research on this topic showing women's greater susceptibility to stress and psychological health symptoms [134][135][136].…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence to suggest that interventions in women at risk of antenatal depression were effective in preventing postnatal depression and also improving pregnancy outcomes [26][27][28]. Subsequently, several systematic reviews and meta-analyses substantiated the above observation [29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…However, there were no systematic reviews on the effectiveness of PPE with the initial education regarding ISPs on infant and postpartum parental sleep and depression delivered from pregnancy to 1 month postpartum. The participants in 2 systematic reviews 5,17 did not meet our inclusion criteria. Reuter et al found inconsistencies in the effectiveness of PPE delivered before and/or after birth on ISPs 5 .…”
Section: Introductionmentioning
confidence: 99%
“…5 However, they included studies in which the education was first imparted to parents of infants aged 4-6 months who were already experiencing ISPs. Sasaki et al 17 examined the effects of PPE about ISPs on maternal depression, and concluded that the effects of PPE delivered during pregnancy were inconsistent. However, their review was limited to interventions targeting pregnant women.…”
Section: Introductionmentioning
confidence: 99%